A mini review on the generation of crimped ultrathin fibers via electrospinning: Materials, strategies, and applications. (4th March 2020) - Zaarour, Bilal; Zhu, Lei; Huang, Chen; Jin, Xiangyu
Abstract : Structures modification of fibers has been attracting significant attention in various fields and applications. Among different techniques of fabricating ultrathin fibers, electrospinning is the most commonly adopted method because of the ease of forming fibers with a wide range of properties and its exceptional advantages, such as the ability to spin into different shapes and sizes, as well as the adaptable porosity of electrospun fiber webs. The crimped structure has been attracting the attention of scientific researchers owing to its unique properties (eg, spring‐like behavior, supreme strain, remarkable specific surface area, good piezoelectric properties, excellent biological properties, and so on). Therefore, this study summarizes a review of the strategies and methods, reported so far, of generating electrospun crimped ultrathin fibers of various polymers. The review focuses on the polymer types, formation methods, characterizations, and applications of the electrospun crimped ultrathin fibers. We believe this work can serve as an important reference for the materials, strategies, and applications of crimped fibers.